Collisional mechanism of ligand release by Bombyxmori JHBP, a member of the TULIP / Takeout family of lipid transporters. (February 2020) - Dupas, Stéphane; Neiers, Fabrice; Granon, Emma; Rougeux, Erwan; Dupont, Sébastien; Beney, Laurent; Bousquet, François; Shaik, Haq Abdul; Briand, Loic; Wojtasek, Hubert; Charles, Jean-Philippe
Abstract: Juvenile hormones (JHs) regulate important processes in insects, such as postembryonic development and reproduction. In the hemolymph of Lepidoptera, these lipophilic sesquiterpenic hormones are transported from their site of synthesis to target tissues by high affinity carriers, the juvenile hormone binding proteins (JHBPs). Lepidopteran JHBPs belong to a recently uncovered, yet very ancient family of proteins sharing a common lipid fold (TULIP domain) and involved in shuttling various lipid ligands. One important, but poorly understood aspect of JHs action, is the mechanism of hormone transfer to or through the plasma membranes of target cells. Since many membrane-active peptides and proteins, such as the pore-forming bacterial toxins, are activated by low pH or interaction with phospholipid membranes, we have examined the effect of these factors on JH binding by JHBPs. The affinity of Bombyx mori and Manduca sexta JHBPs for JH III was determined by the DCC assay, equilibrium dialysis, and isothermal titration calorimetry, and found to be greatly reduced at low pH, in agreement with previous observations. Loss of binding was accompanied by changes in fluorescence and near-UV CD spectra, indicating significant changes in protein structure in the environment of aromatic residues. The apparent dissociation rate constant (koff ) of the JHBP-JH III complex was greater at acidic pH, suggesting that low pH favors ligand release by opening of the binding pocket. The affinity of recombinant B. mori JHBP (r Bm JHBP) was also decreased in the presence of anionic phospholipid vesicles. Measurements of steady-state fluorescence anisotropy with the lipophilic probe TMA-DPH demonstrated that r Bm JHBP specifically interacts with anionic membranes. These results suggest the existence of a collisional mechanism for ligand release that may be important for delivery of JHs to the target cells, and could be relevant to the function of related members of this emerging family of lipid-transport proteins. Graphical abstract: Image 1 Highlights: Juvenile hormone binding proteins (JHBPs) show conserved sensitivity to acidic pH. Low pH triggers a conformational change in B. mori JHBP. B. mori JHBP interacts with phospholipid membranes. Low pH and anionic phospholipid membranes both reduce affinity of B. mori JHBP for JH III. A collisional mechanism of JH release by JHBPs to target cells is proposed.